Descriptive analysis of horses and ponies attending horse auctions in Victoria from July 2019 to March 2020. Issue 1 (29th September 2022) - Chapman, GR; Wells, B; Gilkerson, JR; Flash, ML
Abstract : Introduction: In recent years there has been public speculation about the breed, destination and number of horses being sold by public auction at livestock saleyards in Australia. Currently, there is little objective information available about the breed and condition of horses sold through this medium. With little publicly available objective data on these horses, the horse industry has been left vulnerable to misinformation. Accurate information regarding the composition and condition of horses attending saleyards is important to identify and address any welfare issues and to inform public debate. Method: Data were collected on 312 horses and ponies presented for sale through the Pakenham Horse Sales between July 2019 and March 2020. All horses and ponies were inspected at the saleyards and information on breed, age, body condition score (BCS), purchaser and sale price were recorded as the animals were auctioned. Results: Crossbred horses and ponies were the largest groups presented for sale. Ponies were more likely to be sold to private buyers. Quarter horses and riding ponies were as likely to be sent to slaughter as thoroughbreds and standardbreds. Entire males and females sold for lower prices than geldings. Most horses and ponies (64%) were sold to private buyers. More than three‐quarters (77%) of horses and ponies presented for sale had a BCS greater than or equal to three out of five. Conclusion: This pilot study challenges perceptions that thoroughbreds are the primary breed to attend public sales or that animals attending the sales are in poor condition.